PREDIKSI NILAI KERUSAKAN PERKERASAN LENTUR DENGAN METODE MEKANISTIK-EMPIRIK (STUDI KASUS : REKONSTRUKSI JL. ARTERI SELATAN) - , CITRA KHARISMA P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are various ways to predict damage of roads in Indonesia. One of the new methods is developed, namely the mechanistic-empirical method. The first phase is calculate the pavement response in terms of stress, strain and deflection critical each pavement layer by using the analysis method based on the mechanistic principles of elastic theory. The second phase is predict the performance of structure and function of the pavement in the future which is a function of traffic load and environmental influences around it. In this study, the damage will be predicted is the Reconstruction of the South Arterial Road. Preliminary analysis is to the data volume and traffic load. Pavement material data, soil data and weather-climate is used as an input parameter KENPAVE. The output from running KENPAVE is used to determine the stress-strain response that occurs as a result of the traffic load as the basic analysis method of MEPDG (mechanistic-empirical Pavement Design Guide) to determine the value of repetition that occurs in the area of review and predict the type of damage that occurs in year-n. Then, predict the design life of the type of damage that occurs in year-n. Maximum stress-strain response of alligator cracking causes for 2,019E-04, longitudinal cracking 2,670E-04 and rutting 1,584E-03. South Arterial Road at the beginning of pavement age in 2013 occurs alligator cracking at 0.682% and at the end of the pavement life plan for 10 years (in 2022) of 16,325%. Longitudinal cracking, in 2013, damage occurs along 0,137 ft/ mil and 2022 is predicted at 6,404 ft/ mil. While, the magnitude of rutting, in 2013 deep as 0,071 and in 2022 is predicted at 0.746 in. Based on the design criteria of the AASHTO 2008, pavement design life of South Arterial Road will be damaged alligator cracking and rutting exceeding the maximum of tolerance limit before the 7th year of a 10-year design life. So, before the 7th year, the pavement should be fixed so the further damage does not exist.